Korelasi Nahdlatul Ulama (NU) dan Muhammadiyah - M. Ali Imron; M. Fadhil Akbar; Nurul Fitria; Agus Rifki Ridwan (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2025)
This research aims to compare the role of Nahdlatul Ulama (NU) and Muhammadiyah in politics in Indonesia. This study belongs to library study research type of research conducted to write, clarify, and collect data from many reported data sources, both unwritten and written. The data were collected through the so-called literature study. Citing and analyzing data with this documentation technique aims to search, collect, and process data from written documents such as books, journals, and other written sources. The results revealed that NU and Muhammadiyah have depicted their respective roles in politics in Indonesia since their inception. The differences could be seen from several comparisons, such as ideology, background, reasons for formation, and orientation. Moreover, NU and Muhammadiyah have provided a tangible impact on Indonesian society. Subsequently, the differences in ideology have had a different impact in politics.